The effect of previous experience with working in groups on students’ academic performance in the accounting discipline - María José Martínez-Romero; Alba Mª Priego de la Cruz; Cristina Ferrer-García; Mª Pilar Casado-Belmonte (Revista de Contabilidad: Spanish Accounting Review, 2021)
This paper analyses the implementation of cooperative learning techniques in accounting subjects to investigate whether students’ willingness to work in groups, based on their perceptions regarding this learning technique arising from previous group working experiences, are related to their academic performance. The findings reveal that students’ perceptions regarding their improved skills due to having worked in groups are positively and significantly related to their academic performance; meanwhile students’ perceptions of having learnt from others are negatively and significantly related to their academic performance. Therefore, this study extends the existing literature on cooperative learning and students’ academic performance by considering students’ attitudes toward working in groups resulting from their prior experiences.